High-temperature-resistant high-toughness epoxy adhesive film and preparation method thereof

By using modified liquid epoxy resin and composite filler in epoxy film, the problems of brittlement and insufficient toughness of traditional epoxy films at high temperatures are solved, and the effects of high temperature stability and toughness are achieved.

CN119391318AActive Publication Date: 2025-02-07SHANGHAI HAIYING ADHESIVE TECH CO LTD

Patent Information

Application Number
CN202411639095.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-07
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

Traditional epoxy films are prone to brittle, deform or fail at high temperatures, and have poor toughness and are difficult to withstand the application requirements in complex stress environments.

Method used

By preparing a formula epoxy film, including modified liquid epoxy resin, solid epoxy resin, composite filler and compatibility agent, the composite filler forms high melting point magnesium oxide and montmorillonite by calcining the mixture of magnesium phosphate and montmorillonite and Magnesium silicate increases the high temperature resistance of the filler; carbon fiber is added to improve toughness.

Benefits of technology

The high temperature resistance and toughness of the epoxy film are significantly improved, so that it maintains stability and strength in a high-temperature environment, and can better withstand external impacts and complex stresses.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005137947700000091
    Figure BDA0005137947700000091
Patent Text Reader

Abstract

The invention relates to a high-temperature-resistant high-toughness epoxy adhesive film and a preparation method thereof, and belongs to the technical field of epoxy adhesive films. The high-temperature resistance and mechanical strength of the filler are remarkably improved by calcining a mixture of magnesium phosphate, glucose and montmorillonite at a high temperature, filler agglomeration is reduced by a carbonaceous film formed by carbonizing glucose, and the dispersity and compatibility are improved; after the carbon fibers are pretreated by nitric acid, the interface bonding force between the carbon fibers and the resin matrix and the calcined montmorillonite is enhanced, and the overall toughness of the composite filler is improved; and the composite filler forms a skeleton structure in a resin matrix, so that the toughness and high temperature resistance of the epoxy adhesive film are effectively improved. Besides, the polyamic acid is added into the epoxy resin, and the high temperature resistance and toughness of the epoxy resin are further improved through the formation of a semi-interpenetrating network structure or chemical bond action by utilizing the characteristic that a polyamic acid molecular chain segment can maintain relatively good mechanical properties at high temperature; the prepared epoxy adhesive film is suitable for various application scenes with high-temperature and high-toughness requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of epoxy films and relates to a high-temperature resistant and high-toughness epoxy film and a preparation method thereof. Background Art

[0002] Epoxy film, as a one-component epoxy adhesive containing a latent curing agent, achieves bonding and curing by heating to induce a cross-linking polymerization reaction. Due to its high bonding rigidity and wide applicability, it occupies an important position in the fields of aerospace, high-speed rail interiors, and cruise ship manufacturing. Traditional liquid epoxy adhesives have been gradually optimized into dry one-component epoxy film forms due to uneven manual glue application and cumbersome operation, aiming to improve operational convenience and uniformity. However, epoxy film products currently on the market face many technical challenges. For example, traditional epoxy films are prone to brittleness, deformation, and even failure at high temperatures, and cannot meet the use requirements in some high-temperature environments. At the same time, its toughness is relatively poor, and it is difficult to withstand large external force shocks or vibrations, resulting in limited applications in complex stress environments. Summary of the invention

[0003] The purpose of the present invention is to provide a high-temperature resistant and high-toughness epoxy film and a preparation method thereof, which has the characteristics of high toughness, high temperature resistance, simple manufacturing process and environmental protection.

[0004] The purpose of the present invention can be achieved by the following technical solutions:

[0005] A high-temperature resistant and high-toughness epoxy film, the formula of the epoxy film is as follows: in parts by weight, 55-65 parts of modified liquid epoxy resin, 20-30 parts of solid epoxy resin, 5-10 parts of composite filler, 3-5 parts of compatibilizer, 2-3 parts of curing agent, 0.5-1 part of accelerator,

[0006] The preparation method of the composite filler is as follows:

[0007] S1-1: 10-15 parts by weight of montmorillonite was placed in 85-90 parts by weight of deionized water, and ultrasonicated for 30 minutes. Then, 1-3 parts by weight of magnesium phosphate pentahydrate and 0.5-1 parts by weight of glucose were added, and ultrasonically stirred at 90° C. for 1.5 hours. The mixture was allowed to stand at room temperature for 1 hour, washed with deionized water, dried in a vacuum drying oven at 60° C., and then calcined in a muffle furnace. The mixture was then ball-milled in a ball mill for 1-2 hours at a ball mill speed of 400-500 r / min to obtain powder A.

[0008] S1-2: adding 3 to 5 parts by weight of carbon fiber to 20 to 30 parts by weight of nitric acid solution, ultrasonicating for 30 minutes, washing with deionized water until the pH of the eluent is 7, and drying in a vacuum drying oven at 60° C. for 6 hours to obtain pretreated carbon fiber;

[0009] S1-3: Powder A and pretreated carbon fiber are mixed, placed in a ball mill for ball milling for 1.5 hours at a ball milling speed of 500-600 r / min, and passed through a 200-mesh sieve to obtain the composite filler.

[0010] Furthermore, the calcination temperature in the muffle furnace in S1-1 is 400-500°C, and the calcination time is 30 minutes.

[0011] Furthermore, the concentration of the nitric acid solution in S1-2 is 2M.

[0012] Furthermore, the powder A and the pretreated carbon fiber in S1-3 are mixed in a mass ratio of 2:1.

[0013] Furthermore, the preparation method of the modified liquid epoxy resin is as follows:

[0014] The temperature is raised to 70° C. and 10 to 15 parts by weight of polyamic acid are added to 50 to 60 parts by weight of liquid bisphenol A epoxy resin under stirring conditions of 800 to 1000 r / min, 0.5 to 1 part by weight of 1M acetic acid solution is added dropwise, and stirring is maintained for 1.5 to 2 hours to obtain the modified liquid epoxy resin.

[0015] Furthermore, the solid epoxy resin is one or more of solid bisphenol A epoxy resin, solid bisphenol F epoxy resin, and solid bisphenol S epoxy resin.

[0016] Furthermore, the compatibilizer is one of the silane coupling agents KH550, KH560, and KH570.

[0017] Furthermore, the curing agent is superfine dicyandiamide.

[0018] Furthermore, the accelerator is an imidazole curing accelerator.

[0019] A method for preparing a high-temperature resistant and high-toughness epoxy film comprises the following steps:

[0020] S10-1: Mix the modified liquid epoxy resin, solid epoxy resin, composite filler and coupling agent according to the formula ratio, heat to 70°C and stir at 750-850 r / min for 30 min, then add the curing agent and accelerator, keep at 70°C and stir at 850-950 r / min for 1 h to obtain a rubber compound;

[0021] S10-2: coating the adhesive on the polytetrafluoroethylene film and drying it naturally to obtain the high temperature resistant and high toughness epoxy adhesive film.

[0022] In the process of preparing the composite filler, magnesium phosphate and glucose are first mixed with montmorillonite and calcined in a high temperature environment. Under high temperature, magnesium phosphate decomposes to produce magnesium oxide and water, of which magnesium oxide is a high melting point compound that can significantly improve the high temperature resistance of the filler; at the same time, since the radius of magnesium ions is similar to the original cations between the montmorillonite layers, some magnesium ions can replace the original cations and enter the montmorillonite layers to form magnesium silicate; this process not only changes the interlayer structure of montmorillonite, but also enhances the mechanical strength of the filler through the chemical bonds formed between magnesium ions and silicates. In addition, glucose will undergo a carbonization reaction at high temperature to form a layer of carbon film wrapped on the surface of the filler particles. This layer of carbon film can not only reduce the agglomeration between the filler particles and improve its dispersibility in the resin matrix, but also enhance the compatibility between the filler and the resin matrix. Carbon fiber, as another reinforcing material, needs to be pretreated with nitric acid before being added. Nitric acid can remove impurities on the surface of the carbon fiber, and increase its surface area and roughness through etching, thereby improving the interfacial bonding between the carbon fiber and the resin matrix and the calcined montmorillonite. This strong interfacial bonding helps the carbon fiber to effectively transfer and disperse stress when subjected to external forces, thereby improving the overall toughness of the composite filler. The composite filler forms a skeleton structure in the resin matrix, which can significantly improve the toughness and high temperature resistance of the epoxy film.

[0023] When polyamic acid is mixed with epoxy resin, the molecular segments of the two interact with each other through physical entanglement and chemical bonding. Physical entanglement refers to the interlacing and entanglement of the molecular segments of polyamic acid and epoxy resin in space to form a semi-interpenetrating network structure; chemical bonding occurs between the carboxyl group of polyamic acid and the epoxy group in epoxy resin. With the interaction between the molecular segments of polyamic acid and epoxy resin, the crosslinking density of the system gradually increases, which increases the number of crosslinking points in the epoxy resin system and makes the connection between the molecular segments closer, thereby improving the overall performance of the material. In addition, the amide group in the molecular segment of polyamic acid has high thermal stability and can maintain good mechanical properties at high temperatures. When polyamic acid and epoxy resin form a semi-interpenetrating network structure, this thermal stability will be transmitted to the entire system. At the same time, due to the increase in crosslinking density, the movement of the molecular segments is restricted, reducing the possibility of slippage and breakage of the molecular chain at high temperatures, and significantly improving the high temperature resistance of epoxy resin. The addition of polyamic acid salt can also improve the microstructure of epoxy resin. By optimizing the mixing process and reaction conditions, the molecular chain segments of polyamic acid and epoxy resin can be more evenly and densely distributed on a microscopic scale, which helps to improve the overall performance and stability of the material. When subjected to external impact, the molecular chain segments of polyamic acid can absorb and disperse energy through deformation and slippage, thereby playing a toughening role, allowing the epoxy resin to maintain high strength and hardness while also having strong flexibility and impact resistance. In addition, the reaction of polyamic acid and epoxy resin can generate groups that promote the curing of epoxy resin and reduce the curing temperature of the system.

[0024] Beneficial effects of the present invention:

[0025] (1) By calcining a mixture of magnesium phosphate, glucose and montmorillonite at high temperature, high-melting-point magnesium oxide is generated and replaces the interlayer cations of montmorillonite to form magnesium silicate, which significantly improves the high-temperature resistance and mechanical properties of the filler; at the same time, the carbon film formed by carbonization of glucose reduces the agglomeration of the filler and improves its dispersibility and compatibility; after pretreatment with nitric acid, the carbon fiber enhances the interfacial bonding strength with the resin matrix and the calcined montmorillonite, further improving the overall toughness of the composite filler; the skeleton structure formed by the composite filler in the resin matrix effectively improves the toughness and high-temperature resistance of the epoxy film.

[0026] (2) The addition of polyamic acid can improve the high temperature resistance and toughness of epoxy resin. By forming a semi-interpenetrating network structure or chemical bonding, the polyamic acid molecular segments can maintain good mechanical properties at high temperatures and absorb and disperse external impacts. DETAILED DESCRIPTION

[0027] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0028] In the following examples and comparative examples:

[0029] Solid bisphenol A epoxy resin, solid bisphenol F epoxy resin, solid bisphenol S epoxy resin, liquid bisphenol A epoxy resin: purchased from Jiaxing Dongfang Resin Factory;

[0030] Silane coupling agents KH550, KH560, and KH570: purchased from Hebei Yanxi Chemical Co., Ltd.;

[0031] Ajinomoto latent curing agent MY-25: purchased from Benlong Shoji (Tianjin) International Trade Co., Ltd.;

[0032] Polytetrafluoroethylene membrane: purchased from Forsman Science (Beijing) Co., Ltd.

[0033] Superfine dicyandiamide: purchased from Wuhan Xinyang Ruihe Chemical Technology Co., Ltd.;

[0034] Polyamic acid: purchased from Merck KGaA, Darmstadt, Germany;

[0035] Acetic acid: purchased from Merck KGaA, Darmstadt, Germany;

[0036] Carbon fiber: purchased from Beijing Mairida Technology Co., Ltd.;

[0037] Montmorillonite: purchased from Jiangsu Xiansheng Pharmaceutical Co., Ltd.

[0038] Magnesium phosphate pentahydrate: purchased from Shanghai Haohong Biopharmaceutical Technology Co., Ltd.;

[0039] Glucose: purchased from CSPC Pharmaceutical Group Shengxue Glucose Co., Ltd.

[0040] Example 1

[0041] A high-temperature resistant and high-toughness epoxy film, the epoxy film has a formula 1 as follows: in parts by weight, 60 parts of modified liquid epoxy resin, 25 parts of solid bisphenol A epoxy resin, 7 parts of composite filler, 4 parts of silane coupling agent KH550, 2.5 parts of ultrafine dicyandiamide, 0.7 parts of Ajinomoto latent curing agent MY-25,

[0042] The preparation method of the composite filler is as follows:

[0043] S1-1: 12 parts by weight of montmorillonite was placed in 87 parts by weight of deionized water, ultrasonicated for 30 minutes, then 2 parts by weight of magnesium phosphate pentahydrate and 0.7 parts by weight of glucose were added, ultrasonically stirred at 90°C for 1.5 hours, allowed to stand at room temperature for 1 hour, washed with deionized water and dried in a vacuum drying oven at 60°C, then calcined in a muffle furnace at a calcination temperature of 450°C for 30 minutes, and then ball-milled in a ball mill for 1.5 hours at a ball mill speed of 450 r / min to obtain powder A;

[0044] S1-2: 4 parts by weight of carbon fiber were added to 25 parts by weight of 2M nitric acid solution, ultrasonicated for 30 minutes, washed with deionized water until the pH of the eluent was 7, and dried in a vacuum drying oven at 60° C. for 6 hours to obtain pretreated carbon fiber;

[0045] S1-3: Powder A and pretreated carbon fiber were mixed in a mass ratio of 2:1, placed in a ball mill for 1.5 hours at a ball mill speed of 550 r / min, and passed through a 200-mesh sieve to obtain the composite filler.

[0046] The preparation method of the modified liquid epoxy resin is as follows:

[0047] The temperature was raised to 70° C. and 12 parts by weight of polyamic acid were added to 55 parts by weight of liquid bisphenol A epoxy resin under stirring at 900 r / min, 0.7 parts by weight of 1M acetic acid solution was added dropwise, and stirring was maintained for 1.7 hours to obtain the modified liquid epoxy resin.

[0048] A method for preparing a high-temperature resistant and high-toughness epoxy film comprises the following steps:

[0049] S10-1: According to formula 1, the modified liquid epoxy resin, solid bisphenol A epoxy resin, composite filler and silane coupling agent KH550 were mixed, heated to 70°C and stirred at 800 r / min for 30 min, and then superfine dicyandiamide and Ajinomoto latent curing agent MY-25 were added, maintained at 70°C and stirred at 900 r / min for 1 h to obtain a rubber compound;

[0050] S10-2: coating the adhesive on the polytetrafluoroethylene film and drying it naturally to obtain the high temperature resistant and high toughness epoxy adhesive film.

[0051] Example 2

[0052] A high-temperature resistant and high-toughness epoxy film, the formula 2 of the epoxy film is as follows, in parts by weight, 55 parts of modified liquid epoxy resin, 20 parts of solid bisphenol F epoxy resin, 5 parts of composite filler, 3 parts of silane coupling agent KH560, 2 parts of ultrafine dicyandiamide, 0.5 parts of Ajinomoto latent curing agent MY-25,

[0053] The preparation method of the composite filler is as follows:

[0054] S1-1: 10 parts by weight of montmorillonite was placed in 85 parts by weight of deionized water, ultrasonicated for 30 minutes, then 1 part by weight of magnesium phosphate pentahydrate and 0.5 parts by weight of glucose were added, ultrasonically stirred at 90°C for 1.5 hours, allowed to stand at room temperature for 1 hour, washed with deionized water and dried in a vacuum drying oven at 60°C, then calcined in a muffle furnace at a calcination temperature of 400°C for 30 minutes, and then ball-milled in a ball mill for 1 hour at a ball mill speed of 400 r / min to obtain powder A;

[0055] S1-2: 3 parts by weight of carbon fiber were added to 20 parts by weight of 2M nitric acid solution, ultrasonicated for 30 minutes, washed with deionized water until the pH of the eluent was 7, and dried in a vacuum drying oven at 60° C. for 6 hours to obtain pretreated carbon fiber;

[0056] S1-3: Powder A and pretreated carbon fiber were mixed in a mass ratio of 2:1, placed in a ball mill for 1.5 hours at a ball mill speed of 500 r / min, and passed through a 200-mesh sieve to obtain the composite filler.

[0057] The preparation method of the modified liquid epoxy resin is as follows:

[0058] The temperature was raised to 70° C. and 10 parts by weight of polyamic acid was added to 50 parts by weight of liquid bisphenol A epoxy resin under stirring at 800 r / min, and 0.5 parts by weight of 1M acetic acid solution was added dropwise, and stirring was maintained for 1.5 hours to obtain the modified liquid epoxy resin.

[0059] A method for preparing a high-temperature resistant and high-toughness epoxy film comprises the following steps:

[0060] S10-1: According to formula 2, the modified liquid epoxy resin, solid bisphenol F epoxy resin, composite filler and silane coupling agent KH560 were mixed, heated to 70°C and stirred at 750 r / min for 30 min, and then superfine dicyandiamide and Ajinomoto latent curing agent MY-25 were added, maintained at 70°C and stirred at 850 r / min for 1 h to obtain a rubber compound;

[0061] S10-2: coating the adhesive on the polytetrafluoroethylene film and drying it naturally to obtain the high temperature resistant and high toughness epoxy adhesive film.

[0062] Example 3

[0063] A high-temperature resistant and high-toughness epoxy film, the formula 3 of the epoxy film is as follows, in parts by weight, 65 parts of modified liquid epoxy resin, 30 parts of solid bisphenol S epoxy resin, 10 parts of composite filler, 5 parts of silane coupling agent KH570, 3 parts of ultrafine dicyandiamide, 1 part of Ajinomoto latent curing agent MY-25,

[0064] The preparation method of the composite filler is as follows:

[0065] S1-1: 15 parts by weight of montmorillonite was placed in 90 parts by weight of deionized water, ultrasonicated for 30 minutes, then 3 parts by weight of magnesium phosphate pentahydrate and 1 part by weight of glucose were added, ultrasonically stirred at 90°C for 1.5 hours, allowed to stand at room temperature for 1 hour, washed with deionized water and dried in a vacuum drying oven at 60°C, then calcined in a muffle furnace at a calcination temperature of 500°C for 30 minutes, and then ball-milled in a ball mill for 2 hours at a ball mill speed of 500 r / min to obtain powder A;

[0066] S1-2: 5 parts by weight of carbon fiber were added to 30 parts by weight of 2M nitric acid solution, ultrasonicated for 30 minutes, washed with deionized water until the pH of the eluent was 7, and dried in a vacuum drying oven at 60° C. for 6 hours to obtain pretreated carbon fiber;

[0067] S1-3: Powder A and pretreated carbon fiber were mixed in a mass ratio of 2:1, placed in a ball mill for 1.5 hours at a ball mill speed of 600 r / min, and passed through a 200-mesh sieve to obtain the composite filler.

[0068] The preparation method of the modified liquid epoxy resin is as follows:

[0069] The temperature was raised to 70° C. and 15 parts by weight of polyamic acid were added to 60 parts by weight of liquid bisphenol A epoxy resin under stirring at 1000 r / min, 1 part by weight of 1M acetic acid solution was added dropwise, and stirring was maintained for 2 hours to obtain the modified liquid epoxy resin.

[0070] A method for preparing a high-temperature resistant and high-toughness epoxy film comprises the following steps:

[0071] S10-1: According to formula 3, the modified liquid epoxy resin, solid bisphenol S epoxy resin, composite filler and silane coupling agent KH570 were mixed, heated to 70°C and stirred at 850 r / min for 30 min, then superfine dicyandiamide and Ajinomoto latent curing agent MY-25 were added, maintained at 70°C and stirred at 950 r / min for 1 h to obtain a rubber compound;

[0072] S10-2: coating the adhesive on the polytetrafluoroethylene film and drying it naturally to obtain the high temperature resistant and high toughness epoxy adhesive film.

[0073] Comparative Example 1

[0074] The liquid epoxy resin was not modified, and the remaining steps were the same as those in Example 1.

[0075] Comparative Example 2

[0076] No carbon fiber is added in the preparation of the composite filler, and the remaining steps are consistent with Example 1.

[0077] Comparative Example 3

[0078] Magnesium phosphate pentahydrate was not added in the preparation of the composite filler, and the remaining steps were consistent with those in Example 1.

[0079] Comparative Example 4

[0080] No composite filler was added, and the remaining steps were the same as those in Example 1.

[0081] Performance Testing

[0082] The plane tensile strength and shear strength of the embodiments and comparative examples were measured according to GB / T 1452-2005 sandwich structure flat tensile strength test method and GB / T 7124-1986 adhesive tensile shear strength test method. The shear test piece was 2.0 mm thick LY12 hard aluminum material, and the flat-pulled aluminum plate was 1 mm thick pure aluminum plate.

[0083]

[0084] It can be seen from the data of the examples and comparative examples that the epoxy film prepared by using a composite filler formed by modifying a liquid epoxy resin with polyamic acid and blending a calcined product of montmorillonite and magnesium phosphate with carbon fiber has higher toughness and high temperature resistance.

[0085] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. A high temperature resistant and high toughness epoxy film, characterized in that: The formula of the epoxy film is as follows: by weight, 55-65 parts of modified liquid epoxy resin, 20-30 parts of solid epoxy resin, 5-10 parts of composite filler, 3-5 parts of compatibilizer, 2-3 parts of curing agent, 0.5-1 part of accelerator, The preparation method of the composite filler is as follows: S1-1: 10-15 parts by weight of montmorillonite was placed in 85-90 parts by weight of deionized water, and ultrasonicated for 30 minutes. Then, 1-3 parts by weight of magnesium phosphate pentahydrate and 0.5-1 parts by weight of glucose were added, and ultrasonically stirred at 90° C. for 1.5 hours. The mixture was allowed to stand at room temperature for 1 hour, washed with deionized water, dried in a vacuum drying oven at 60° C., and then calcined in a muffle furnace. The mixture was then ball-milled in a ball mill for 1-2 hours at a ball mill speed of 400-500 r / min to obtain powder A. S1-2: adding 3 to 5 parts by weight of carbon fiber to 20 to 30 parts by weight of nitric acid solution, ultrasonicating for 30 minutes, washing with deionized water until the pH of the eluent is 7, and drying in a vacuum drying oven at 60° C. for 6 hours to obtain pretreated carbon fiber; S1-3: Powder A and pretreated carbon fiber are mixed, placed in a ball mill for ball milling for 1.5 hours at a ball milling speed of 500-600 r / min, and passed through a 200-mesh sieve to obtain the composite filler.

2. The high temperature resistant and high toughness epoxy film according to claim 1, characterized in that: The calcination temperature in the muffle furnace in S1-1 is 400-500°C, and the calcination time is 30 minutes.

3. The high temperature resistant and high toughness epoxy film according to claim 1, characterized in that: The concentration of the nitric acid solution in S1-2 is 2M.

4. The high temperature resistant and high toughness epoxy film according to claim 1, characterized in that: In the S1-3, the powder A and the pretreated carbon fiber are mixed in a mass ratio of 2:

1.

5. The high temperature resistant and high toughness epoxy film according to claim 1, characterized in that: The preparation method of the modified liquid epoxy resin is as follows: The temperature is raised to 70° C. and 10 to 15 parts by weight of polyamic acid are added to 50 to 60 parts by weight of liquid bisphenol A epoxy resin under stirring conditions of 800 to 1000 r / min, 0.5 to 1 part by weight of 1M acetic acid solution is added dropwise, and stirring is maintained for 1.5 to 2 hours to obtain the modified liquid epoxy resin.

6. The high temperature resistant and high toughness epoxy film according to claim 1, characterized in that: The solid epoxy resin is one or more of solid bisphenol A epoxy resin, solid bisphenol F epoxy resin and solid bisphenol S epoxy resin.

7. The high temperature resistant and high toughness epoxy film according to claim 1, characterized in that: The compatibilizer is one of the silane coupling agents KH550, KH560 and KH570.

8. The high temperature resistant and high toughness epoxy film according to claim 1, characterized in that: The curing agent is superfine dicyandiamide.

9. The high temperature resistant and high toughness epoxy film according to claim 1, characterized in that: The accelerator is an imidazole curing accelerator.

10. A method for preparing a high temperature resistant and high toughness epoxy film according to any one of claims 1 to 9, characterized in that: The steps include: S10-1: Mix the modified liquid epoxy resin, solid epoxy resin, composite filler and coupling agent according to the formula ratio, heat to 70°C and stir at 750-850 r / min for 30 min, then add the curing agent and accelerator, keep at 70°C and stir at 850-950 r / min for 1 h to obtain a rubber compound; S10-2: coating the adhesive on the polytetrafluoroethylene film and drying it naturally to obtain the high temperature resistant and high toughness epoxy adhesive film.

Citation Information

Patent Citations

  • Method for synthesizing end-anhydride epoxy resin curing agent

    CN105131288A

  • Novel epoxy adhesive film and preparation method thereof

    CN111286282A

  • Room-temperature-cured bi-component epoxy adhesive with high heat resistance and high peel strength

    CN112300740A

  • High-temperature-resistant and deformation-resistant chip epoxy adhesive film and preparation method thereof

    CN117025117A

  • Medium-temperature curing high-modulus epoxy resin matrix and preparation method thereof

    CN118374124A

Cited By

  • Impact-resistant epoxy structural adhesive

    CN121379463A